The concept of den'gi (money) in the St. Petersburg population at the beginning of the 1990s - Renate Rathmayr (Journal for East European Management Studies, 2004)
Social change brings about discursive change. Particularly, it causes shifts of meaning within the key concepts of social discourse. The concept of den'gi (money) has undergone fundamental alteration in Russian language and culture since perestroika. This conceptual change will be discussed in the following article. My findings are based on a corpus of interviews recorded in St. Petersburg in 1993. The concepts compared, i.e. the concept of den'gi before and after perestroika, respectively, can only be sketched out roughly here. The interviews conducted in 1993 reveal conflicting discourses on money that are rooted in Russian, Soviet-Russian - the traces of the minor role money played in the Soviet era were still present in social discourse in 1993 - and free enterprise ideologies, respectively. They also reveal that by that time a clear tendency towards a concept of money oriented by market economy had already emerged, at least among the younger urban population. – – Gesellschaftliche Veränderungen verändern Diskurse und insbesondere ihre Schlüssel-konzepte. Das Konzept den'gi (money) hat im Russischen nach der Perestroika eine gewaltige Veränderung erfahren. Worin diese besteht, wird im Beitrag anhand eines Korpus von Interviews, die im Jahr 1993 in Sankt Petersburg aufgezeichnet wurden, nachgezeichnet. Die beiden zur Kontrastierung herangezogenen Konzepte bzw. Epochen vor und nach der Perestrojka können in diesem Rahmen nur ansatzweise skizziert werden. Die Interviews des Jahres 1993 zeigen die Präsenz der widerstreitenden Diskurse über Geld, die ihre Wurzeln in der russischen und russisch-sowjetischen - die Spuren der geringen Bedeutung von Geld in der Sowjetzeit sind deutlich präsent - sowie marktwirtschaftichen Ideologie haben, und deutlich in die Richtung der Durchsetzung eines marktwirtschaftlich orientierten Konzepts den'gi zumindest für die jüngere Bevölkerung der Großstädte weisen.
Keywords: 650; Linguistic concepts; Linguistic change; Discourse analysis; Language and society; Russian language